The effects of cooperative learning on enhancing reading comprehension skills for the first-year non-english majored students at Mekong University = - Bùi, Thị Nhật Tuyền (Can Tho University, 2009)
The purpose of this study was to examine whether cooperative learning method enhanced students reading comprehension skill. This was an experimental research, which was conducted on one group pre- and post-test design. The search instruments used to collect the data were pre-test and post-test on reading omprehension skill, pre- and post- questionaire, interview, group evaluation form, and lesson evaluation form.